Preparation and application of bottom anti-reflection coating with high etching rate
By using a doping bottom anti-reflective coating formed by blending aliphatic polyol glycidyl ether polymer and aromatic epoxy, the problem of insufficient dry etching rate and process adaptability in the prior art is solved, and the effects of high etching rate and low temperature curing are achieved.
Patent Information
- Application Number
- CN202411930334.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-14
AI Technical Summary
The existing bottom anti-reflective coatings have shortcomings in terms of dry etching rate and process adaptability, and cannot meet the requirements of low-temperature baking of compound semiconductor substrates.
Using a doping bottom anti-reflective coating based on blending of aliphatic polyol glycidyl ether polymer and aromatic epoxy, the dry etching rate is improved and cured under low temperature conditions is achieved.
The preparation of a high etching rate bottom anti-reflective coating is realized, the process flow is simplified, the dry etching rate is improved, and the low-temperature baking requirements of compound semiconductor substrates are met.
Smart Images

Figure CN119620541A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photolithography, and in particular to the preparation and application of a bottom anti-reflection coating with a high etching rate. Background Art
[0002] Bottom anti-reflective coating is a functional material used in the photolithography process. With the rapid development of integrated circuit chip manufacturing technology, the photolithography patterns produced by the photolithography process based on single-layer photoresist cannot meet the actual production needs due to the standing wave effect caused by the bottom reflected light. Therefore, it is necessary to cooperate with anti-reflective coating to achieve fine control of the photoresist pattern; the application of bottom anti-reflective coating can effectively eliminate the above-mentioned influence, improve the morphology of the photoresist pattern after development, improve the resolution and line width uniformity of the photoresist pattern, and ultimately improve the performance and yield of the chip in the process stage.
[0003] According to the difference in etching process, bottom anti-reflective coating can be divided into dry etching and wet etching. Due to the anisotropic characteristics of dry etching, the pattern morphology after etching is steeper and there is no problem such as side hollowing or footing. Therefore, it is more widely used in conventional processes.
[0004] In recent years, with the development of semiconductor technology, the miniaturization of photolithography patterns has also put forward higher requirements on the properties of bottom anti-reflective coatings, including:
[0005] 1. It has specific absorption of light and rays, effectively reducing reflection efficiency and eliminating standing wave effect;
[0006] 2. No mixing with photoresist and no interface defects;
[0007] 3. It has a faster dry etching rate than photoresist, which increases the process window;
[0008] 4. It can have a wider process tolerance and adapt to various types of substrates.
[0009] Therefore, in order to solve the above problems, various types of anti-reflective coating products have been developed on the market, mainly including: main chain type, graft type and doping type. The graft type is the mainstream type of anti-reflective graphics at present, which is mainly prepared based on the compounding of polyacrylic acid graft copolymers; the graft type anti-reflective coating can dynamically control the performance of the product by changing the proportion of copolymer monomers. However, the preparation of the product involves a complex polymerization process, the dry etching rate needs to be further improved, the process adaptability is poor, and it cannot meet the requirements of low-temperature baking of compound semiconductor substrates, including:
[0010] 1. Poor selectivity with photoresist and slow etching rate;
[0011] 2. Requires complex synthetic polymerization process;
[0012] 3. The curing temperature is high and cannot adapt to the compound substrate;
[0013] 4. Poor matching and prone to interface anomalies. Summary of the invention
[0014] In order to overcome the above defects, the present invention provides a method for preparing a bottom anti-reflective coating with a high etching rate, which is a doped bottom anti-reflective coating formed by blending an aliphatic polyol glycidyl ether polymer and an aromatic epoxy. The method has a simple preparation process and does not require a complicated polymerization process. The introduction of the aliphatic polyol glycidyl ether polymer can effectively reduce the carbon content ratio in the system and quickly improve the dry etching rate of the coating. At the same time, the curing temperature of the system is low, and curing can occur under conventional baking conditions (such as: 120°C), which well meets the requirements of low-temperature baking of compound semiconductor substrates.
[0015] The present invention provides a bottom anti-reflective coating with a high etching rate, comprising the following components in percentage by weight: 5-15% of a solid phase, 85-94% of a solvent, and 0-1% of a surfactant;
[0016] The solid phase is composed of the following components in parts by weight: 2.5-10.5 parts of aliphatic polyol glycidyl ether polymer, 0-3 parts of small molecule glycidyl ether polymer, 1.5-6 parts of aromatic ring epoxy compound, and 0.2-1.0 parts of thermal acid generator.
[0017] Furthermore, the aliphatic polyol glycidyl ether polymer is one or more of polyglycerol diglycidyl ether, polyglycerol glycidyl ether, polypropylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, and methoxy polyethylene glycol glycidyl ether.
[0018] Further, the small molecule glycidyl ether polymer is one or more of ethylene glycol diglycidyl ether, trimethylolpropane (1.1.1-trimethylolpropane) triglycidyl ether, 1,3-diglycidyl ether glycerol, trimethylolpropane triglycidyl ether, pentaerythritol glycidyl ether, 1,4-butanediol glycidyl ether, propylene glycol triglycidyl ether, 1,2-cyclohexanedicarboxylic acid diglycidyl ether, propylene glycol diglycidyl ether, 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate, 1,4-cyclohexanedimethanol diglycidyl ether, and 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester.
[0019] Furthermore, the aromatic ring epoxy compound is one or more of 1,6-naphthol diglycidyl ether, 9,10-anthraquinone diglycidyl ether, 2,6-anthraquinone diglycidyl ether, biphenyl bisphenol diglycidyl ether, bisphenol A diglycidyl ether, and trisphenol triglycidyl ether.
[0020] Furthermore, the thermal acid generator is one or more of 2-nitrobenzyl toluenesulfonate, benzoin toluenesulfonate, pyridinium p-toluenesulfonate, 2,4,4,6-tetrabromocyclohexanedione, and organic alkyl sulfonate.
[0021] Further, the solvent is ethyl acetate, butyl acetate, ethyl lactate, butyl lactate, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, methyl acetate cellosolve, ethyl acetate cellosolve, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol, propylene glycol monomethyl ether (PGME), propylene glycol monoethyl ether, propylene glycol monomethyl ether acetate (PGMEA), propylene glycol propyl ether acetate, methyl 2-hydroxy-3-methylbutyric acid, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, ethyl 3-ethoxypropionate, methyl 3-ethoxypropionate, methyl pyruvate, ethyl pyruvate, ethyl 2-hydroxypropionate, ethyl 2-hydroxy-2-methylpropionate, ethyl ethoxyacetate, ethyl hydroxyacetate, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-pyrrolidone, toluene, xylene, methyl ethyl ketone, cyclopentanone, and cyclohexanone. One or more.
[0022] Further, the surfactant is a nonionic surfactant or a fluorine-containing surfactant;
[0023] The nonionic surfactant is one or more of polyoxyethylene sorbitan acid esters such as polyoxyethylene alkyl ether, polyoxyethylene stearyl ether, polyoxyethylene cetyl ether, polyoxyethylene sorbitan monolaurate, polyoxyethylene oleyl ether, polyoxyethylene alkyl aryl ether, polyoxyethylene lauryl ether, sorbitan fatty acid ester, polyoxyethylene sorbitan tristearate, polyoxyethylene sorbitan trioleate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, etc.;
[0024] Fluorine-containing surfactants include AsahiGuard (registered trademark) AG710, Sumlon (registered trademark) S-382, SC101, SC102, SC103, SC104, SC105, SC106 (available from Asahi Glass Co..Ltd.), organosiloxane polymer KP341 (available from Shin-Etsu Chemical Co..Ltd.); Fluorad FC430, FC431 (available from Sumitomo 3M, Ltd.); Eftop (registered trademark) EF301, EF303, EF352 (available from Mitsubishi Materials Electronic Chemicals Co., Ltd.), MEGAFACE (registered trademark) F171, F173, R-30, R-30N and R-40-LM (available from DIC Corporation).
[0025] Wherein polyoxyethylene alkyl aryl ether includes polyoxyethylene octylphenol ether and polyoxyethylene benzylphenol ether;
[0026] Sorbitan fatty acid esters include sorbitan monooleate, sorbitan trioleate, sorbitan monolaurate, sorbitan tristearate, sorbitan monostearate, sorbitan monopalmitate.
[0027] A method for preparing a bottom anti-reflective coating with a high etching rate comprises the following steps:
[0028] Step 1, weigh each component according to proportion;
[0029] Step 2: Mix the above components evenly, use a filter membrane to filter after they are completely dissolved, and obtain a bottom anti-reflective coating solution after cyclic filtration, and store it at low temperature away from light until it is tested;
[0030] Step 3: Spin-coat the bottom anti-reflective coating solution on the wafer, and then bake and solidify it to obtain an anti-reflective coating film.
[0031] Furthermore, in step 2, a magnetic stirrer is used for mixing, the speed is set to 500 r / min, and the stirring time is 30 min to ensure that all components are evenly dispersed.
[0032] This solution also discloses the application of a bottom anti-reflective coating with a high etching rate in the field of photolithography.
[0033] (III) Technical Effect
[0034] The above structure enables this solution to have the following beneficial effects:
[0035] 1. The preparation process is simple and does not require a complicated polymerization process;
[0036] 2. The introduction of aliphatic polyol glycidyl ether polymer can effectively reduce the carbon content in the system and quickly increase the dry etching rate of the coating;
[0037] 3. Use epoxy system, high curing efficiency, low temperature baking curing, meet the requirements of low temperature baking of compound semiconductor substrate. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0039] Figure 1 Photoresist slice pattern without anti-reflective coating
[0040] Figure 2A group of embodiments of the present scheme are provided with a slicing pattern of an upper layer of photoresist. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0042] A bottom anti-reflective coating with a high etching rate comprises the following components in percentage by weight: 5-15% of a solid phase, 85-95% of a solvent, and 0-1% of a surfactant;
[0043] The solid phase is composed of the following components in parts by weight: 2.5-10.5 parts of aliphatic polyol glycidyl ether polymer, 0-3 parts of small molecule glycidyl ether polymer, 1.5-6 parts of aromatic ring epoxy compound, and 0.2-1.0 parts of thermal acid generator.
[0044] Example 1: Take 10 parts of polyethylene glycol diglycidyl ether, 1 part of pentaerythritol glycidyl ether, 2 parts of trimethylolpropane triglycidyl ether, 6 parts of 2,6-anthraquinone diglycidyl ether, 1 part of 2,4,4,6-tetrabromocyclohexanedienone, 11 parts of KP34, and 179 parts of propylene glycol methyl ether acetate, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0045] Example 2: Take 10 parts of polyglycerol glycidyl ether, 1 part of pentaerythritol glycidyl ether, 2 parts of trimethylolpropane glycidyl ether, 6 parts of 2,6-anthraquinone diglycidyl ether, 1 part of 2,4,4,6-tetrabromocyclohexanedienone, 11 parts of KP34, and 179 parts of propylene glycol methyl ether acetate, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0046] Example 3: Take 10 parts of polypropylene glycol diglycidyl ether, 1 part of pentaerythritol glycidyl ether, 2 parts of trimethylolpropane glycidyl ether, 6 parts of 2,6-anthraquinone diglycidyl ether, 1 part of 2,4,4,6-tetrabromocyclohexanedienone, 11 parts of KP34, and 179 parts of propylene glycol methyl ether acetate, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0047] Example 4: Take 10 parts of methoxypolyethylene glycol glycidyl ether, 1 part of pentaerythritol glycidyl ether, 2 parts of trimethylolpropane glycidyl ether, 6 parts of 2,6-anthraquinone diglycidyl ether, 1 part of 2,4,4,6-tetrabromocyclohexanedienone, 11 parts of KP34, and 179 parts of propylene glycol methyl ether acetate, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0048] Example 5: Take 10 parts of polyglycerol diglycidyl ether, 1 part of pentaerythritol glycidyl ether, 2 parts of trimethylolpropane glycidyl ether, 6 parts of 2,6-anthraquinone diglycidyl ether, 1 part of 2,4,4,6-tetrabromocyclohexanedienone, 11 parts of KP34, and 179 parts of propylene glycol methyl ether acetate, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0049] Take 2 mL of each sample prepared in Examples 1-5, spin coat it on a 4-inch wafer at 3000 rpm, bake it on a 200°C hot plate for 60 seconds, and then test the film thickness with a film thickness meter and the n and k values of the film at a wavelength of 248 nm with an ellipsometer.
[0050] Table 1 Test values of Examples 1-5
[0051]
[0052] Example 6: Take 20 parts of polyglycerol glycidyl ether, 2 parts of pentaerythritol glycidyl ether, 6 parts of 2,6-anthraquinone diglycidyl ether, 1 part of 2,4,4,6-tetrabromocyclohexanedienone, 11 parts of KP34, 70 parts of propylene glycol methyl ether acetate, and 100 parts of cyclopentanone, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0053] Example 7: Take 20 parts of polyglycerol glycidyl ether, 2 parts of trimethylolpropane glycidyl ether, 6 parts of 2,6-anthraquinone diglycidyl ether, 1 part of 2,4,4,6-tetrabromocyclohexanedienone, 11 parts of KP34, 70 parts of propylene glycol methyl ether acetate, and 100 parts of cyclopentanone, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0054] Example 8: Take 14 parts of polyglycerol glycidyl ether, 2 parts of 1,2-cyclohexanedicarboxylic acid diglycidyl ester, 4 parts of 2,6-anthraquinone diglycidyl ether, 1 part of 2,4,4,6-tetrabromocyclohexanedienone, 11 parts of KP34, 89 parts of propylene glycol methyl ether acetate, and 89 parts of cyclopentanone, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0055] Example 9: Take 14 parts of polyglycerol glycidyl ether, 2 parts of 1,4-cyclohexanedimethanol diglycidyl ether, 4 parts of 2,6-anthraquinone diglycidyl ether, 1 part of 2,4,4,6-tetrabromocyclohexanedienone, 11 parts of KP34, 89 parts of propylene glycol methyl ether acetate, and 89 parts of cyclopentanone, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0056] Example 10: Take 14 parts of polyglycerol glycidyl ether, 2 parts of 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester, 4 parts of 2,6-anthrol diglycidyl ether, 1 part of 2,4,4,6-tetrabromocyclohexanedienone, 11 parts of KP34, and 178 parts of propylene glycol methyl ether acetate, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0057] Example 11: Take 8 parts of polyglycerol glycidyl ether, 2 parts of 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexylcarboxylate, 2 parts of 2,6-anthraquinone diglycidyl ether, 1 part of 2,4,4,6-tetrabromocyclohexanedienone, 11 parts of KP34, and 186 parts of propylene glycol methyl ether acetate, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0058] Example 12: Take 8 parts of polyglycerol glycidyl ether, 2 parts of ethylene glycol diglycidyl ether, 2 parts of 2,6-anthrol diglycidyl ether, 1 part of 2,4,4,6-tetrabromocyclohexanedienone, 1 part of polyoxyethylene hexadecyl ether, and 186 parts of propylene glycol monomethyl ether, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0059] Example 13: Take 8 parts of polyglycerol glycidyl ether, 2 parts of glycerol triglycidyl ether, 2 parts of 2,6-anthraquinone diglycidyl ether, 1 part of 2,4,4,6-tetrabromocyclohexanedienone, 1 part of polyoxyethylene hexadecyl ether, and 186 parts of propylene glycol monomethyl ether, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0060] Example 14: Take 10 parts of polyglycerol glycidyl ether, 3 parts of propylene glycol diglycidyl ether, 6 parts of 2,6-anthraquinone diglycidyl ether, 1 part of 2,4,4,6-tetrabromocyclohexanedienone, 1 part of polyoxyethylene hexadecyl ether, and 179 parts of propylene glycol monomethyl ether, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0061] Example 15: Take 10 parts of polyglycerol glycidyl ether, 3 parts of 1,4-butanediol glycidyl ether, 6 parts of 2,6-anthraquinone diglycidyl ether, 1 part of 2,4,4,6-tetrabromocyclohexanedienone, 1 part of polyoxyethylene hexadecyl ether, and 179 parts of propylene glycol monomethyl ether, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0062] Take 2 mL of each sample prepared in Examples 6-15, spin-coat it on a 4-inch wafer at 500 rpm, bake it on a 90°C hot plate for 120 s after coating, test the thickness of the anti-reflective coating film with a film thickness meter, and record the test film thickness THK1. After the test is completed, take a certain amount of PGMEA and coat it on the anti-reflective layer film. After standing for 60 s, spin dry the PGMEA, and test the thickness of the anti-reflective layer film again with a film thickness meter. Record the test film thickness THK2, calculate the film thickness change rate of the anti-reflective layer film before and after coating with PGMEA, and the calculation formula is (THK1-THK2) / THK1, and then replace the hot plates at 100°C, 110°C, 120°C, and 150°C respectively to repeat the above steps.
[0063] Table 2 Test values of Examples 6-15
[0064]
[0065] Example 16: Take 10 parts of polypropylene glycol glycidyl ether, 3 parts of pentaerythritol glycidyl ether, 6 parts of 1,6-naphthol diglycidyl ether, 1 part of 2,4,4,6-tetrabromocyclohexanedienone, 1 part of FC430, 1 part of SC103, and 178 parts of butyl acetate, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0066] Example 17: Take 10 parts of polyglycerol glycidyl ether, 3 parts of pentaerythritol glycidyl ether, 6 parts of 9,10-anthraquinone diglycidyl ether, 1 part of 2,4,4,6-tetrabromocyclohexanedienone, 1 part of FC430, 1 part of SC103, and 178 parts of butyl acetate, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0067] Example 18: Take 10 parts of polypropylene glycol glycidyl ether, 3 parts of pentaerythritol glycidyl ether, 6 parts of 2,6-anthraquinone diglycidyl ether, 1 part of 2,4,4,6-tetrabromocyclohexanedienone, 1 part of FC430, 1 part of SC103, and 178 parts of butyl acetate, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0068] Example 19: Take 10 parts of polypropylene glycol glycidyl ether, 3 parts of pentaerythritol glycidyl ether, 6 parts of bisphenol A diglycidyl ether, 1 part of 2,4,4,6-tetrabromocyclohexanediene ketone, 1 part of FC430, 1 part of SC103, and 178 parts of butyl acetate, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0069] Example 20: Take 10 parts of polypropylene glycol glycidyl ether, 3 parts of pentaerythritol glycidyl ether, 6 parts of biphenyl bisphenol diglycidyl ether, 1 part of 2,4,4,6-tetrabromocyclohexanedienone, 1 part of FC430, 1 part of SC103, and 178 parts of butyl acetate, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0070] Example 21: Take 10 parts of polypropylene glycol glycidyl ether, 3 parts of pentaerythritol glycidyl ether, 6 parts of trisphenol triglycidyl ether, 1 part of 2,4,4,6-tetrabromocyclohexanediene ketone, 1 part of FC430, 1 part of SC103, and 178 parts of butyl acetate, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0071] Take 2 mL of each sample prepared in Examples 16-21, spin-coat it on a 4-inch wafer at 3000 rpm, bake it on a 200°C hot plate for 60 s after coating, and then test the film thickness with a film thickness meter and the NK value of the film with an ellipsometer. The test wavelength of Examples 16, 17, and 18 is 248 nm, and the test wavelength of Examples 19, 20, and 21 is 193 nm.
[0072] Table 3 Test values of Examples 16-21
[0073]
[0074] Example 22: Take 10 parts of polyglycerol glycidyl ether, 3 parts of pentaerythritol glycidyl ether, 6 parts of 2,6-anthraquinone diglycidyl ether, 1 part of 2,4,4,6-tetrabromocyclohexanedienone, 11 parts of KP34, 1 part of R-30, and 178 parts of propylene glycol methyl ether acetate, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0075] Example 23: Take 10 parts of polyglycerol glycidyl ether, 3 parts of pentaerythritol glycidyl ether, 6 parts of 2,6-anthraquinone diglycidyl ether, 1 part of benzoin toluenesulfonate, 11 parts of KP34, 1 part of R-30, and 178 parts of propylene glycol methyl ether acetate, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0076] Example 24: Take 10 parts of polyglycerol glycidyl ether, 3 parts of pentaerythritol glycidyl ether, 6 parts of 2,6-anthraquinone diglycidyl ether, 1 part of 2-nitrobenzyl toluenesulfonate, 11 parts of KP34, 1 part of R-30, and 178 parts of propylene glycol methyl ether acetate, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0077] Example 25: Take 10 parts of polyglycerol glycidyl ether, 3 parts of pentaerythritol glycidyl ether, 6 parts of 2,6-anthraquinone diglycidyl ether, 1 part of pyridinium p-toluenesulfonate, 11 parts of KP34, 1 part of R-30, and 178 parts of propylene glycol methyl ether acetate, mix them in the above proportions, seal and stir, use a filter membrane after complete dissolution, and after circulating filtration, store at low temperature and away from light until testing.
[0078] Take 20 mL of each sample prepared in Examples 22-25 and store it at low temperature and away from light. Take 2 mL of each sample and spin coat it on a 4-inch wafer at 3000 rpm. After coating, bake it on a hot plate at 200°C for 60 seconds, and then test the film thickness with a film thickness meter. After 3 months, take 2 mL of each sample and repeat the coating steps to test the film thickness.
[0079] The silicon wafer coated with the anti-reflective coating in Examples 22-25 was etched according to the following etching process conditions, and the upper photoresist was compared to complete the evaluation of the photoresist / anti-reflective coating etching ratio, as shown in Table 4; etching conditions: power 500W, RF power 300W, CHF350sccm / CF4150sccm, etching time 30 seconds.
[0080] Table 4 Test values of Examples 22-25
[0081]
[0082] Comparative Example: Commercial photoresist SEPR602 was coated on a silicon wafer, and the baking conditions were 95°C for 90 seconds, and the post-baking temperature was 120°C for 60 seconds; ASML850 exposure machine was used for exposure 0.7NA-0.89PC, 2.38% TMAH was used as the developer, and the development time was 60 seconds. The slice pattern was observed, as shown in FIG. Figure 1 shown.
[0083] Example 22 was coated on a silicon wafer, and the baking condition was 190°C for 60 seconds. The upper layer was coated with commercial photoresist SEPR602, and the baking condition was 95°C for 90 seconds. The post-baking temperature was 120°C for 60 seconds. ASML850 exposure machine was used for exposure 0.7NA-0.89PC, 2.38% TMAH was used as the developer, and the development time was 60 seconds. Compared with comparative example 1, the slice pattern was observed, as shown in FIG. Figure 2 As shown, the photoresist combined with the anti-reflective coating of this solution can effectively improve the standing wave effect and optimize the profile of the upper photoresist.
[0084] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high etch rate bottom anti-reflective coating, characterized in that: The composition comprises the following components in percentage by weight: 5-15% solid phase, 85-94% solvent, and 0-1% surfactant; The solid phase is composed of the following components in parts by weight: 2.5-10.5 parts of aliphatic polyol glycidyl ether polymer, 0-3 parts of small molecule glycidyl ether polymer, 1.5-6 parts of aromatic ring epoxy compound, and 0.2-1.0 parts of thermal acid generator.
2. The high etch rate bottom anti-reflection coating according to claim 1, characterized in that: The aliphatic polyol glycidyl ether polymer is one or more of polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, polyglycerol diglycidyl ether, methoxy polyethylene glycol glycidyl ether, and polyglycerol glycidyl ether.
3. The high etch rate bottom anti-reflection coating according to claim 1, characterized in that: The small molecule glycidyl ether polymer is one or more of ethylene glycol diglycidyl ether, 1,3-diglycidyl ether glycerol, pentaerythritol glycidyl ether, 1,4-butanediol glycidyl ether, propylene glycol triglycidyl ether, trimethylolpropane triglycidyl ether, 1,2-cyclohexanedicarboxylic acid diglycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester, 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexylcarboxylate, propylene glycol diglycidyl ether, and trimethylolpropane (1.1.1-trimethylolpropane) triglycidyl ether.
4. The high etch rate bottom anti-reflection coating according to claim 1, characterized in that: The aromatic ring epoxy compound is one or more of 1,6-naphthol diglycidyl ether, 9,10-anthraquinone diglycidyl ether, 2,6-anthraquinone diglycidyl ether, biphenyl bisphenol diglycidyl ether, bisphenol A diglycidyl ether, and trisphenol triglycidyl ether.
5. The high etch rate bottom anti-reflection coating according to claim 1, characterized in that: The thermal acid generator is one or more of 2,4,4,6-tetrabromocyclohexanedienone, benzoin toluenesulfonate, 2-nitrobenzyl toluenesulfonate, pyridinium p-toluenesulfonate, and organic alkyl sulfonate.
6. The high etch rate bottom anti-reflection coating according to claim 1, characterized in that: The solvent is one or more of ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, methyl cellosolve acetate, ethyl cellosolve acetate, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, propylene glycol, propylene glycol monomethyl ether (PGME), propylene glycol monoethyl ether, propylene glycol monomethyl ether acetate (PGMEA), propylene glycol propyl ether acetate, toluene, xylene, methyl ethyl ketone, cyclopentanone, cyclohexanone, ethyl 2-hydroxypropionate, ethyl 2-hydroxy-2-methylpropionate, ethyl ethoxyacetate, ethyl hydroxyacetate, methyl 2-hydroxy-3-methylbutyric acid, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, ethyl 3-ethoxypropionate, methyl 3-ethoxypropionate, methyl pyruvate, ethyl pyruvate, ethyl acetate, butyl acetate, ethyl lactate, butyl lactate, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-pyrrolidone.
7. The high etch rate bottom anti-reflection coating according to claim 1, characterized in that: The surfactant is a nonionic surfactant or a fluorine-containing surfactant.
8. A method for preparing a bottom anti-reflection coating with a high etching rate according to claims 1-7, characterized in that: The steps include: Step 1, weigh each component according to proportion; Step 2, mixing the above components evenly to obtain a bottom anti-reflection coating solution; Step 3: Spin-coat the bottom anti-reflective coating solution on the wafer, and then bake and solidify it to obtain an anti-reflective coating film.
9. The method for preparing a bottom anti-reflection coating with a high etching rate according to claim 8, characterized in that: In step 2, a magnetic stirrer is used for mixing, the speed is set to 500 r / min, and the stirring time is 30 min.